2011
DOI: 10.3324/haematol.2010.039396
|View full text |Cite
|
Sign up to set email alerts
|

LPL is the strongest prognostic factor in a comparative analysis of RNA-based markers in early chronic lymphocytic leukemia

Abstract: The online version of this article has a Supplementary Appendix. BackgroundThe expression levels of LPL, ZAP70, TCL1A, CLLU1 and MCL1 have recently been proposed as prognostic factors in chronic lymphocytic leukemia. However, few studies have systematically compared these different RNA-based markers. Design and MethodsUsing real-time quantitative PCR, we measured the mRNA expression levels of these genes in unsorted samples from 252 newly diagnosed chronic lymphocytic leukemia patients and correlated our data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 42 publications
(48 reference statements)
4
45
0
Order By: Relevance
“…The prognostic value of CLLU1 mRNA expression has previously been investigated in four retrospective studies, 13,15,16,20 including between 59 and 252 patients each and at a median follow-up from diagnosis of between 43 and 102 months. The end-points in all four studies were time to first treatment and overall survival from diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prognostic value of CLLU1 mRNA expression has previously been investigated in four retrospective studies, 13,15,16,20 including between 59 and 252 patients each and at a median follow-up from diagnosis of between 43 and 102 months. The end-points in all four studies were time to first treatment and overall survival from diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] In particular, the expression of genes such as CLLU1, ADAM29 and LPL have recently been associated with different outcomes in CLL. [12][13][14][15][16][17] CLLU1 located at chromosome 12q22, encodes a novel transcript, which has been identified as a marker specific to CLL. 18 In particular, high CLLU1 expression (CLLU1-H) is significantly more frequent in unmutated IGHV and CD38 + CLL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, LPL is frequently overexpressed in invasive cervical squamous cell carcinomas (Carter et al 2012). Most impressively, patients with chronic lymphocytic leukemia (CLL) whose leukemia cells express high levels of LPL transcripts have a lower survival rate (Van Bockstaele et al 2007;Maloum et al 2009;Kaderi et al 2011). One study indicated that high LPL transcript levels in CLL are associated with increased LPL protein production; however, enzymatic activity assays suggested that much of the LPL could be inactive (Mansouri et al 2010).…”
Section: Lipolysis In Cancer and Cancer Cachexiamentioning
confidence: 99%
“…Thus, the study of this gene may be important for a better understanding of the disease variability, and could be used in combination with other markers, adding further information to those provided by established prognostic factors. In this line, an association between SEPT10 and LPL [9], which overexpression was related to adverse clinical outcome in CLL [25], have been previously described, suggesting that SEPT10 could direct LPL to the cell surface by establishing a link between proteoglycans (the cell surface LPL receptor) and the actin cytoskeleton [5,9]. The understanding of biological mechanism of the disease will contribute to future risk stratification strategies with potential value in treatment decisions.…”
Section: Discussionmentioning
confidence: 79%